Original articleToll-like receptors as an innate immunity bridge to neuroinflammation in medulloblastoma - Maslinska, Danuta; Laure-Kamionowska, Milena; Maslinski, Slawomir (Folia Neuropathologica, 2012)
The relationship between inflammation, immunity and cancer is widely accepted but mechanisms mediating this relationship remain unknown. Our present study was undertaken to examine the presence and distribution of Toll-like receptors (TLRs) in necrotic areas of medulloblastoma. These receptors fulfil the criteria postulated for the receptors of innate immunity and signalling from TLRs induces synthesis of various pro-inflammatory cytokines, enzymes and mediators. The study was performed on human medulloblastoma samples containing areas of necrosis within the tumour and/or within the normal nerve tissue at the periphery of the tumour. Proteins of four TLRs: TLR 2, 3, 4 and 9 were detected in the tissue with the immunohistochemical method using the specific antibodies. Two types of necrotic areas were found. In the first type, the area of dead cells was surrounded by undifferentiated medulloblastoma cells. A lot of these cells expressed TLR 2 and TLR 3 antigens. TLR 2 was also expressed on the wall of de novo formed blood vessels that fill tumour regions already cleared from dead cells. The second type of necrotic areas were found at the periphery of the tumour and composed of normal nerve tissue cells. TLR 2, TLR 3 and TLR 9 were detected in hypertrophic glia cells. Our findings show a new function of TLRs as sensors of pathogens released by medulloblastoma dead cells. This new function may provide a key link connecting innate immunity, neuroinflammation and angiogenesis in the tumour.